Pengaruh Sistem Informasi Akuntansi Dan E-Commerce Terhadap Kinerja UMKM Di Kota Jayapura - Jesika Nikita C Saerang; Juliana Waromi; Ulfah Rizky Muslimin (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This research aims to determine the extent of the influence of accounting information systems and e-commerce on the performance of MSMEs in Jayapura City. The research uses a quantitative method. Data collection was conducted using questionnaires. The sampling technique employed was purposive sampling. The population in this research consists of MSME business actors in Jayapura City, and based on Slovin's formula, the sample size was determined to be 100 respondents. The hypothesis testing analysis technique used was bootstrapping with the SmartPLS 4.0 application. The results of this study indicate that the use of accounting information systems and e-commerce has a positive and significant influence on the performance of MSMEs. The conclusions of this study show that 1) the accounting information system has a positive and significant effect on the performance of MSMEs, 2) e-commerce has a positive and significant effect on the performance of MSMEs, 3) accounting information systems and e-commerce simultaneously influence the performance of MSMEs in Jayapura City, suggesting that businesses should consider using accounting and sales tools through accounting information systems and e-commerce to develop their operations.